Strategi Pemasaran untuk Meningkatkan Penjualan Beton Siap Pakai (Ready Mix Concrete) pada PT Semen Indogreen Sentosa Plant Cikarang - A Riyanto; Arman Paramansyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2020)
ABSTRACT The problem to be answered in this study is the strategic factors that exist in the company which includes analysis of the external and internal environment to find alternative strategies that can increase sales. In line with the problem, this research was conducted using descriptive methods, which tend to describe the problems that occur in the company. To solve the problems that occur in the company, the External Strategic Factor Analysis (EFAS), Internal Strategic Factor Analysis (IFAS) and SWOT Analysis are used. The analysis shows that based on internal and external analysis of the company, it can be concluded that the main strategy of PT. Semen Indogreen Sentosa is a strategy of SO (Strength Opportunities) Improving product quality, completeness of distribution facilities, payment terms, product prices and delivery accuracy and low prices with the aim of expanding the market Such as internal factors namely completeness of distribution facilities and field tests, and external factors recruiting workers Experienced and educated experts aim to be able to rival competitors. The results of the analysis show that from the analysis of factors external strategies have. Based on these findings, it was suggested that PT Semen Indogreen Sentosa Plant Cikarang try to improve management's response to its external environment by taking advantage of opportunities arising in the market and also increasing management's response to its internal environment by utilizing the company's strengths and implementing alternative strategies summarized in SWOT Matrix Keywords: Marketing Strategy, SWOT Analysis, SWOT Matrix